Vulnerability evaluation and prediction of the water-energy-food-ecology nexus in the Yangtze River Economic Belt based on TOPSIS, neighborhood rough set and support vector machine - Pan, Yue; Chen, Yan; Liu, Yue (Frontiers in Environmental Science, 2022)
With the intensification of human activities, the vulnerability of water, energy, food and ecology systems has become more and more apparent. The research on the vulnerability of the water-energy-food-ecology(WEFE) nexus is significant to realizing regional sustainable development. This study firstly constructs a vulnerability evaluation index system of the WEFE nexus based on the VSD framework and uses the neighborhood rough set(NRS) to reduce the attributes. Then, the TOPSIS model is used to evaluate the vulnerability of the WEFE nexus in the Yangtze River Economic Belt(YREB). Finally, by comparing the training accuracy of the random forest, decision tree and support vector machine(SVM) model, the SVM model is selected to predict the vulnerability of the WEFE nexus under different scenarios in 2025. The results show that from 2008 to 2019, the vulnerability of the WEFE nexus in the YREB showed a fluctuating downward trend. Guizhou, Hubei and Yunnan provinces have the most significant declines, about 21.3%, 18.89% and 16.91%, respectively. In 2025, under the scenario of strong resource management, the vulnerability of the provinces(municipalities) in the YREB will decrease significantly, while the weak and moderate resource management scenarios are not conducive to reducing vulnerability and even worsen. Therefore, in the future, reasonable measures should be taken actively to continuously strengthen the management of water, energy, food and ecological resources and promote the continuous improvement of the vulnerability of the WEFE nexus.